Highly Conductive and Soluble Polymer Synthesized by Copolymerization of Thiophene with Para-Methoxybenzaldehyde Using Clay Catalyst - Djamal Eddine Kherroub; Larbi Bouhadjar; Bouhadjar Boukoussa; Abdelkader Rahmouni; Khadidja Dahmani; Mohammed Belbachir (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
This present research focuses on the synthesis of a new conducting polymer based on the copolymerization of thiophene with para-methoxybenzaldehyde, using a clay as an ecologic catalyst named Maghnite-H+. The catalysis of the reaction by Maghnite-H+ can confer it important benefits, such as the green environment aspect. The reaction was carried out in dichloromethane as a solvent. The new copolymer obtained is a poly (heteroarylene methines) small bandgap polymers precursor. It can be considered as a useful model system for examining the impacts of π-conjugation length on the electronic properties of this type of conjugated polymers. The measurements of the electrical conductivity gave a value of order of 0.0120 W.cm-1, allowing its use in various important applications. The characteristics of the molecular structure and the thermal behavior of the conducting polymer obtained are also discussed using different methods of analysis, such as: proton nuclear magnetic resonance (NMR), Fourier transform infrared (FTIR) spectroscopy, ultraviolet/visible spectroscopy, and thermal gravimetric analysis (TGA).